The Definition of Risk in Innovative Projects - Khantarjian, Sarkis (Bulletin of Yerevan University G: Economics, 2015)
The article summarizes the literature described different approaches to risk assessment of innovative projects and their classification. It is noted that regardless of the industry, for which the risk assessment is conducted, the most important are the stages of manifestation of risk and identify the source of its origin. Presents the formulas for calculating the accumulated net cash flow.
Keywords: risk, assessment, innovative projects